A COMPARATIVE ECONOMIC STUDY OF IMPORTED INFLATION IN THE AGRICULTURAL SECTOR IN GROUP OF ARAB COUNTRIES FOR THE PERIOD (1990-2022) - Tiba Khalaf Al-Jbouriy, Tiba Khalaf Al-Jbouriy; Basim Hazam Hameed Al-Bahri, Basim Hazam Hameed Al-Bahri (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The research aimed to compare imported inflation in the agricultural sector in Iraq and Jordan, where data collected for time series for the period (1990-2022) and using ARDL model. The results showed a positive and significant relationship between imported inflation and both the price index of agricultural imports, agricultural product, population, agricultural trade openness and exchange rate in the short and long terms in Iraq, the variables were significant in the short term in Jordan, but in the long term some variables were not identical to economic logic, It turns out that there is a long-term equilibrium relationship between the dependent variable and some illustrative variables because not all variables have a long-term equilibrium relationship. The research recommended doing more researches and studies on inflation in the agricultural sector in Iraq and Jordan and more Arab countries and searching for other economic variables affecting inflation in the agricultural sector and reducing inflation rates that affect the agricultural sector which reflects positively on the Iraqi and Jordanian economies; Also supporting agricultural products prices and providing a subsidy for agricultural inputs for the purpose of increasing local production, developing the local economy and reducing imported inflation resulting from the increase in food and agricultural imports.